Pengaruh Latihan Interval Terhadap Peningkatan Kapasitas Aerobik Pada Atlet Ekstra Sepak Bola Usia 16–18 Tahun 2025 - Ni Putu Intiari; I Wayan Artanayasa; I Ketut Semarayasa (Jurnal Sporta Saintika, 2026)
This study aims to investigate the impact of interval training on improving aerobic capacity in soccer players aged 16 to 18 years. The method used was a quasi-experiment with a pretest-posttest design in a control group. For this study, 30 athletes were selected through purposive sampling, with the requirements of being actively training, in good health, and willing to participate in the program. The sample was then randomly divided into two groups, namely the experimental group (n=15) who underwent an interval training program for six weeks, and the control group (n=15) who carried out conventional training. The tool used was the Multistage Fitness Test (beep test) to measure VO₂max. The data were analyzed using paired t-tests and unpaired t-tests using SPSS at a significance level of α = 0.05. The results showed that the experimental group experienced a significant increase in VO₂max, from an average of 42.1 ml/kg/minute to 47.6 ml/kg/minute, while the control group only increased from 42.3 ml/kg/minute to 43.5 ml/kg/minute. The statistical analysis results provided evidence of a significant difference between the two groups (p < 0.05). Therefore, it can be concluded that interval training is effective in increasing the aerobic capacity of youth soccer players. These findings recommend that interval training be integrated into physical training programs at soccer academies to support continuous improvement in athletes' performance and endurance.